Edaphic, structural and physiological contrasts across Amazon Basin forest–savanna ecotones suggest a role for potassium as a key modulator of tropical woody vegetation structure and function - J. Lloyd (Biogeosciences, 2015)
Sampling along a precipitation gradient in tropical South America extending from ca. 0.8 to 2.0 m a−1, savanna soils had consistently lower exchangeable cation concentrations and higher C / N ratios than nearby forest plots. These soil differences were also reflected in canopy averaged leaf traits with savanna trees typically having higher leaf mass per unit area but lower mass-based nitrogen (Nm) and potassium (Km). Both Nm and Km also increased with declining mean annual precipitation (PA), but most area-based leaf traits such as leaf photosynthetic capacity showed no systematic variation with PA or vegetation type. Despite this invariance, when taken in conjunction with other measures such as mean canopy height, area-based soil exchangeable potassium content, [K]sa , proved to be an excellent predictor of several photosynthetic properties (including 13C isotope discrimination). Moreover, when considered in a multivariate context with PA and soil plant available water storage capacity (θP) as covariates, [K]sa also proved to be an excellent predictor of stand-level canopy area, providing drastically improved fits as compared to models considering just PA and/or θP. Neither calcium, nor magnesium, nor soil pH could substitute for potassium when tested as alternative model predictors (ΔAIC > 10). Nor for any model could simple soil texture metrics such as sand or clay content substitute for either [K]sa or θP. Taken in conjunction with recent work in Africa and the forests of the Amazon Basin, this suggests – in combination with some newly conceptualised interacting effects of PA and θP also presented here – a critical role for potassium as a modulator of tropical vegetation structure and function.